The Problems of Medical Tourism Development in Armenia - Sargsyan, Satenik (Bulletin of Yerevan University G: Economics, 2014)
The paper analyzes the current state of factors, which determine the medical tourism development in Armenia. Particularly the level of medical and transportation costs, as well as issues of medical and tourism infrastructure development are considered. It is argued that further growth of the medical tourism sector hinges on international accreditation of local health care organizations, implementation of the open skies policy, efficient promotion of the country in global medical tourism market.
Keywords: exports of medical services, medical tourism model, accreditation of health care organizations, open skies policy, country marketing